Pengaruh Pengetahuan Perpajakan, Pengawasan Account Representative, Sosialisasi Perpajakan, dan Penerapan E-Filing Terhadap Kepatuhan Wajib Pajak Orang Pribadi di Masa Pandemi Covid-19 - Luh Putu Yasinta Ristyani; Rencana Sari Dewi (Universitas Pendidikan Ganesha, 2021)
PThe purpose of this study was to determine the effect of tax knowledge, account representative supervision, tax socialization, and e-filing implementation variables on individual taxpayer compliance registered at KPP Pratama Tabanan during the covid-19 pandemic. The research method used in this study is quantitative using primary data in the form of a questionnaire with a Likert scale measurement. This research was conducted on individual taxpayers who are registered as mandatory SPT and have NPWP at KPP Pratama Tabanan. The distribution of the questionnaires was carried out offline and online using Google Forms as an effort to prevent Covid-19. The method of determining the number of samples refers to the table of Isaac and Michael and uses a simple random sampling technique. The data analysis carried out included descriptive statistics, data quality tests, classical assumption tests, and hypothesis testing with the help of the SPSS Statistics 23 program. In this study it was found that tax knowledge, account representative supervision, tax socialization, and the application of e-filing had a positive and significantly to the compliance of Individual Taxpayers partially during the covid-19 pandemic.Keywords: : Tax Knowledge, Account Representative Supervision, Socialization, E-Filing, Individual Taxpayer Compliance, Covid-19